Failure to reach uric acid target of <0.36 mmol/L in hyperuricaemia of gout is associated with elevated total and cardiovascular mortality - Pérez Ruiz, Fernando (RMD Open, 2019)
OBJECTIVE: To determine the impact of achieving serum uric acid (sUA) of <0.36 mmol/L on overall and cardiovascular (CV) mortality in patients with gout. METHODS: Prospective cohort of patients with gout recruited from 1992 to 2017. Exposure was defined as the average sUA recorded during the first year of follow-up, dichotomised as ≤ or >0.36 mmol/L. Bivariate and multivariate Cox proportional hazards models were used to determine mortality risks, expressed HRs and 95% CIs. RESULTS: Of 1193 patients, 92% were men with a mean age of 60 years, 6.8 years’ disease duration, an average of three to four flares in the previous year, a mean sUA of 9.1 mg/dL at baseline and a mean follow-up 48 months; and 158 died. Crude mortality rates were significantly higher for an sUA of ≥0.36 mmol/L, 80.9 per 1000 patient-years (95% CI 59.4 to 110.3), than for an sUA of <0.36 mmol/L, 25.7 per 1000 patient-years (95% CI 21.3 to 30.9). After adjustment for age, sex, CV risk factors, previous CV events, observation period and baseline sUA concentration, an sUA of ≥0.36 mmol/L was associated with elevated overall mortality (HR=2.33, 95% CI 1.60 to 3.41) and CV mortality (HR=2.05, 95% CI 1.21 to 3.45). CONCLUSIONS: Failure to reach a target sUA level of 0.36 mmol/L in patients with hyperuricaemia of gout is an independent predictor of overall and CV-related mortality. Targeting sUA levels of <0.36 mmol/L should be a principal goal in these high-risk patients in order to reduce CV events and to extend patient survival.